Effects of preparation methods on the characteristics of niosomes - Amal Ali Elkordy; Cheng Shu Chaw; Li Key Yeo (University of Huddersfield Press, 2019)
Niosomes are colloidal vesicles that capable of encapsulating drugs as a carrier for drug delivery system. They are formed by self-assembly of a non-ionic surfactant with cholesterol and co-surfactant. In this work, cinnarizine-containing niosomes comprised of sorbitan monostearate (Span® 60), cholesterol and co-surfactant (Cremophor® ELP, Cremophor® RH40 or Solutol® HS15) were prepared using conventional thin film hydration and microfluidic methods. Effects on characteristics of niosomes with the presence of poorly water-soluble drug, cinnarizine in the niosomal formulations prepared using different methods and incorporation of different co-surfactants were studied and compared for their particle size, polydispersity index (PDI) and encapsulation efficiency. Dynamic light scattering was employed for particle size measurements and drug loading studies were analysed using high performance liquid chromatography (HPLC). The morphology of niosomes was characterized using optical light microscopy.